Ageing tests closer to real service conditions using hyper-sensitive microcalorimetry, a case study on EPDM rubber. (March 2023) - Pushp, Mohit; Lönnermark, Anders; Vikegard, Peter; Wei, Xin-Feng; Hedenqvist, Mikael
Abstract: Accelerated thermal ageing (ATA) coupled to mechanical testing is widely used to predict the lifetime of polymeric products. ATA implies that the mechanisms of ageing are the same at accelerated and service conditions, which may often not be the case. Hence, ageing closer to service conditions is of high importance, but require very sensitive tools. Therefore, a high sensitivity microcalorimetry (MC) method was applied here to assess if it can be a possible tool for lifetime/ageing prediction closer to service conditions. We chose to focus on a complex, yet commonly used, ethylene-propylene-diene terpolymer (EPDM) rubber. Arrhenius extrapolation of the heat flow data indicated two regimes at low and high temperature, with the former having the lower activation energy. The heat flow values measured by the MC revealed contributions from processes such as the melting of the antioxidant, its consumption at low temperature and the breakdown of residual peroxide. MC tests on the EPDM indicated a very low degree of oxidation appearing above 100 °C, too low to be observed with infra-red spectroscopy (FTIR), but noticeable with MC. The high sensitivity of the MC techniques enabled detection of early signs of polymer degradation/ageing and other thermally activated processes that take place at or close to service temperatures (such as those in nuclear power plants). The MC tests were combined with other techniques, such as scanning electron microscopy/energy dispersive X-ray spectroscopy, gas chromatography techniques, differential scanning calorimetry and FTIR to further understand the degradation mechanisms. Highlights: Microcalorimetry (MC) was used to reveal the ageing of a filled EPDM. It proved useful in both quasi-isothermal and non-isothermal conditions. Its high sensitivity made it possible to reveal thermal processes on a very small scale. The μW/g level sensitivity can be used to detect early signs of ageing, close to service conditions. MC is promising for more reliable accelerated testing closer to service conditions.